The effect of CaO on the physicochemical and biological properties of β‐SiAlON ceramics. Issue 2 (21st October 2021) - Gao, Jinxing; Ma, Xin; Mu, Jinghua; Xu, Enxia; Zhang, Can; Gao, Lu; Ma, Chengliang; Zhao, Fei; Sun, Xu; Zhang, Liguo
Abstract: To investigate the effects of CaO on the physicochemical and biological properties of β‐SiAlON, β‐SiAlON ceramics containing CaO were prepared using the direct nitriding method. The results of X‐ray powder diffraction and scanning electron microscopy demonstrated that β‐SiAlON remained in the material phase because the addition of Ca did not result in the formation of Ca‐α‐SiAlON. However, CaO promoted the sintering of β‐SiAlON grains and significantly decreased porosity and increased bulk density and compressive strength. According to a chemical stability study, when β‐SiAlON ceramics powder was soaked in deionized water and a cell culture medium, it was noted to have negative electricity. A reaction occurred with the H + and OH − ions in the deionized water, leading to the formation of surface structures, such as Si‐OH, Al‐OH, and N‐H. Moreover, the addition of CaO caused a different chemical reaction among ions or ion groups in the culture medium, and new chemical groups formed on the material surface that interacted with the culture medium, which resulted in an alteration of the zeta potential and surface chemical properties of β‐SiAlON. MC3T3‐E1 cells cultured on the surface of ceramics proved that the cells cannot adhere well to the surface of β‐SiAlON ceramics with CaO, although they could proliferate well around those with only β‐SiAlON. Therefore, the change in the surface chemical properties provides good anticell adhesion ability, which makes β‐SiAlON with CaO a biocompatible material that can be used to prevent contamination caused by cell adhesion, with possible applications in biosensors or biomedical equipment that must be used in sterile environments.